Integrasi Supplier, Produsen, Dan Pelanggan Pada Ukm Keramik Dinoyo Dengan Cloud Computing - Santoso, Purnomo Budi; Choiri, Moch.; Rahman, Arif (Rekayasa Mesin, 2013)
Globalization forces company as well as small medium enterprise (SME) to face broader market competition. Ceramics small medium enterprises at Dinoyo, Malang are categorized as popular and competitive SME in Indonesia. Ceramics SME Dinoyo have to do continous improvement in order to win the market. The improvement must do to the entire supply chain, including the order receive or forecast system, the production process, and the delivery process to customer. Supply chain approach will give advantages on the desicion of optimal inventories level, demand fulfillment, and materials to end products quality ensurance. The advantages will be achieved when there is collaboration among echelon of supply chain which consist of supplier, manufacturer / producer, and customer. The collaboration among supplier, producer, and customer needs an information system to integrate all informations from each of them. The integration information system will provide information about stock level or inventory level to supplier. Cloud Computing based Information System is a solution to build a database which gives an easier and faster access for supplier and customer. Cloud computing is a technology using internet service with a virtual server for data maintainance and aplication.This research aims to design software of information system using cloud computing techonolgy to simplify data and information processing for Ceramics SME Dinoyo. The cloud computing aplication integrate information from supplier, producer, and customer by using database sharing. The database sharing by producer facilitates the collaboration between supplier and producer as well as between producer and customer. This research shows that the cloud computing application takes lower cost compare to manual system applied by Ceramics SME Dinoyo.Keywords: supply chain management, information system management, cloud computing, SME